Homelessness Interventions in Georgia: Rapid Re-Housing, Transitional Housing, and the Likelihood of Returning to Shelter. Issue 6 (2nd November 2017) - Rodriguez, Jason M.; Eidelman, Tessa A.
Abstract: Since 1987, billions of dollars in homeless assistance have been allocated annually by the U.S. federal government. Yet few evaluations of homelessness interventions exist. This study analyzes the likelihood that households in Georgia returned to shelter within two years of leaving one of three interventions: rapid re-housing (RRH), transitional housing (TH), and emergency shelter (ES), with the latter serving as a reference. Using propensity scores, RRH households were matched to comparable TH and ES households. Generalized linear mixed modeling then controlled for household characteristics as well as variation between intervention implementations. We find that the likelihood of returning to shelter did not seem to be affected by whether study households were gradually transitioned or rapidly placed into housing. Additionally, the effect of TH for households without children seems highly dependent on the intervention's implementation, which deserves further study. Our findings are generalizable to a small, better resourced segment of the general homeless population.